2015
DOI: 10.1002/masy.201400189
|View full text |Cite
|
Sign up to set email alerts
|

Pulling DNA: The Effect of Chain Length on the Mechanical Stability of DNA Chain

Abstract: Summary:We have investigated the effect of chain length on the thermal denaturation as well as on mechanical unzipping of double stranded DNA (ds-DNA) molecule. We use a simple nonlinear Peyrard Bishop and Dauxois (PBD) model and calculate the melting temperature as well as the critical force as a function of chain length for different heterogeneous chains. We found that in mechanical unzipping, when a force is applied on an end, there is a length up-to which the effect of applied force sustains. The base pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We also considered different-length DNA molecules in these two geometries. We have found that for DNA confined in a conically shaped pore, the transition temperature is higher for the shorter molecule [46]. For DNA confined in a cylindrical pore, we have found that the transition temperature increases with the length of the molecule.…”
Section: − Gt Gt Gt Gacccgt T At Gcgt Aat T T Aaat T Aga Gcgt Cat T G...mentioning
confidence: 71%
“…We also considered different-length DNA molecules in these two geometries. We have found that for DNA confined in a conically shaped pore, the transition temperature is higher for the shorter molecule [46]. For DNA confined in a cylindrical pore, we have found that the transition temperature increases with the length of the molecule.…”
Section: − Gt Gt Gt Gacccgt T At Gcgt Aat T T Aaat T Aga Gcgt Cat T G...mentioning
confidence: 71%
“…There are two main ways to separate the two strands. Either the strand is pulled with a constant velocity (constant-extension ensemble) or with a constant force (constant-force ensemble) [ 22 , 35 , 36 ]. The microscopic features of unzipping may vary with the choice of ensemble.…”
Section: Introductionmentioning
confidence: 99%